A FORMAÇÃO INICIAL DE PROFESSORES DE GEOGRAFIA E O PIBID: ESTUDO DE CASO DO PROGRAMA NAS UNIVERSIDADES PÚBLICAS DO PARANÁ - SENE, MICHAEL WELLINGTON (2016)
The initial teacher training is a milestone in your professional life. During this period, the teacher apprehends a set of skills that are necessary for his/her pedagogical practice, but, it is not only that that affects the teaching profession; it is also imbricated in the pre-professional experiences and in the work socialization which takes place at school. In this sense, there is an implicit complexity to the training process of the teacher, being fundamental, experiences in which the teacher can be in a constant process of action/reflection/action. The teaching degree courses, however, present different challenges in fulfilling this task. Thus, many policies have been implemented in Brazil seeking to overcome these limits. Among them, the Initiation in Teaching Scholarships Institutional Program (PIBID), in which one of the objectives is to encourage the training of teachers for basic education, contributing to raise the quality of the public school. Considering our interest in understanding these processes linked to the initial formation of the Geography teacher, in this research we analyze the teaching profession and the potentialities of the PIBID on the construction of the necessary knowledges by the teacher to his/her professional practice. For that, we carried out the analysis of the productions and socialized experiences by the PIBID of Geography programs in the state of Paraná from the Public Universities, in the regional events of 2012, 2014 and 2015, as we have also followed the Geography PIBID of UNICENTRO in Guarapuava, between 2014 and 2015. Therefore, we have adopted a qualitative methodology, through the documentary research and case study (GODOY, 1995b; LÜDKE e ANDRÉ, 1986; BARDIN, 2011). The results show that the ITSIP significantly contributes to the professionalism of the Geography teacher, because it allows concrete situations of learning the different skills that are required for the professional practice: theoretical-conceptual deeper understanding of the geographic contents; domains of the research skills in education; creation of teaching materials and methodologies that contribute to the student to understand the geographic space and to build a spatial thinking